On luminescence kinetics of scintillators used in X-ray introscopy systems - Ryzhikov, V.; Starzhinskiy, N.; Seminozhenko, V.; Grinyov, B.; Nagornaya, L.; Spasov, V.; Katrunov, K.; Zenya, I.; Vyagin, O. (Functional Materials, 2004)
Data are presented on the influence of various factors upon luminescence kinetics of scintillator crystals based on activated ZnSe, Csl, CWO and GSO. It is shown that the isovalent dopant type substantially affects the decay times т and afterglow level of ZnSe-based scintillators, and the value of т, depending upon the dopant concentration, can vary from 1 to 150 ps. It has been determined that scintillation kinetics of ZnSe(Te) crystals has peculiar features, being characterized by a non-monotonous decrease with a region of rising luminescence intensity at the initial stage after stopping the irradiat ion of samples. Mechanism of energy transfer has been considered for this case. Decay times of oxide scintillators (CWO, GSO) is essentially dependent both on non-stoichiometry of their composition and on the presence of admixtures. It has been shown that the afterglow level of Csl- and CWO-based scintillators depends both on the dose of preliminary X-ray irradiation and on the density of defects introduced into the crystal mechanically. The ro le of X-ray irradiation and finishing thermal treatment has been considered for optimizati on of luminescence kinetics properties of scintillation elements. Приводятся данные о влиянии различных факторов на кинетику люминесценции кристаллов-сцинтилляторов на основе активированных кристаллов ZnSe, Csl, CWO и GSO. Показано, что тип изовалентной примеси оказывает существенное влияние на времена высвечивания т сцинтилляторов на основе ZnSe, и эта величина в зависимости от концентрации примеси может составлять 1-150 мкс. Определено, что кинетика высвечивания кристаллов ZnSe(Te) имеет особенности и характеризуется немонотонным спадом с наличием участка возрастания интенсивности люминесценции на начальном этапе после прекращения облучения образцов. Рассмотрен механизм энергопереноса данного явления. Инерционность оксидных сцинтилляторов (CWO, GSO) существенно зависит как от нестехиометричности состава, так и наличия неконтролируемых примесей. Показано, что уровень послесвечения сцинтилляторов на основе Csl и CWO зависит как от дозы предварительного рентгеновского облучения, так и от концентрации дефектов, введенных в кристалл механическим способом. Изучена роль финишной термообработки в оптимизации инерционных свойств сцинтилляционных элементов. Наводяться дані про вплив різних факторів на кінєтику люмінесценції кристалів-сцинтиляторів на основі активованих кристалів ZnSe, Csl, CWO та GSO. Показано, що тип ізовалентної домішки впливає на час висвітлення і сцинтиляторів на основі ZnSe, і ця величина у залежності від концентрації домішки може складати 1-150 мкс. Визначено, що кінетика висвітлення кристалів ZnSe(Te) має особливості і характеризується немонотонним спадом з наявністю ділянки зростання інтенсивності люмінесценції на початковому етапі після припинення опромінювання зразків. Розглянуто механізм енергопереносу цього явища. Інерційність оксидних сцинтиляторів (CWO, GSO) суттєво залежить як від нестехіометричності сполуки, так і від неконтрольованих домішок. Показано, що рівень післясвітіння сцинтиляторів на основі Csl i CWO залежить як від дози попереднього рентгенівського опромінення, так і від концентрації дефектів, що введені у кристал механічним способом. Вивчено роль фінішної термообробки в оптимізації інерційних властивостей сцинтиляційних елементів.